ASUHAN KEPERAWATAN KELUARGA DENGAN PENERAPAN TERAPI PENGALIHAN SELF MANAGEMENT PADA TAHAP PERKEMBANGAN KELUARGA REMAJA DENGAN MASALAH KEPERAWATAN PERILAKU KESEHATAN CENDERUNG BERESIKO MEROKOK DI WILAYAH KERJA PUSKESMAS TIBAN BARU KOTA BATAM TAHUN 2024 - Selvita, Venta; Gemini, Savitri (Ensiklopedia of Journal, 2024)
Abstract: Smoking behavior in adolescents is a serious health problem because it has a negative impact on long-term health and quality of life. Families have an important role in shaping and modifying adolescent health behavior. This study aims to implement and evaluate family nursing care with the application of self-management diversion therapy at the stage of family development of adolescents with health behavior problems that tend to be at risk of smoking. The method used in this Professional Scientific Paper is a case study conducted based on the stages of nursing care including assessment, diagnosis, problem priority, intervention, implementation and evaluation of nursing. The results of the case study found problems in the family, namely health behavior that tends to be at risk and ineffective health management, planning that focuses on behavior modification and health education. The results of the implementation showed a decrease in the frequency of smoking in adolescents, an increase in the family's ability to manage health and support changes in adolescent behavior effectively. The evaluation showed that the nursing care approach involving self-management therapy was effective in reducing smoking behavior in adolescents with active support from the family.Keywords: Keperawatan Keluarga, Remaja, Self-management